The Effect of Learning Integers Using Cartoons on 7th Grade Students' Attitude to Mathematics - (:unkn) unknown (EDAM, 2013)
The purpose of this research is to investigate the effect on students' attitudes toward mathematics when cartoons are used in teaching integers. The research was designed in the form of a pre-test and post-test with a quasi experimental control group. The research participant group was composed of sixty-one (61) 7th grade students attending an elementary school in Bolu during the 2008-2009 academic year. Integers were taught during six weeks using seventeen cartoons developed for this study. 7 homogenous groups, each consisting of four students sharing the same opinions, were utilized in order to facilitate more comprehensive discussion on the concepts while at the same time encouraging them to question their own thinking patterns by creating a social learning environment. Data was collected using a Mathematics Attitude Scale and through the written opinions of the students concerning the implementation process. Whereas the quantitative data was analyzed by performing a t-test for dependent and independent samples, the qualitative data was analyzed descriptively. Furthermore, while the method of use of cartoons in teaching math lessons positively affected the interest in the mathematics course, the perceived benefits of mathematics and the perceived mathematics achievement levels, which are the sub-components of the attitude, compared to the conventional teaching, the conventional teaching method led to a decline in students' interest in the mathematics course. When the students were asked to describe their feelings toward cartoon based teaching, they responded by saying that they enjoyed the cartoons and that they increased their interest in the math lesson. In light of the findings of this study, the researchers have developed suggestions for those who are to conduct further research on cartoons.
Keywords: Attitude towards Mathematics; Cartoon; Mathematics Teachings; Integers